Comparison of ropivacaine with ropivacaine–dexamethasone combination for postoperative analgesia in the pectoral nerve block for modified radical mastectomy: A randomized clinical trial - Veena Mathur; Brijesh Kumari; Anand Kumar Verma; Arvind Khare; Deepak Kumar Garg (The Indian Anaesthetists' Forum)
Background and Aims: The pectoral nerve block types I and II are novel techniques to provide analgesia for modified radical mastectomy (MRM) surgeries performed under general anesthesia. The primary objective of this study was to compare the duration of effective analgesia, and the secondary objectives were to evaluate the total amount of rescue analgesics in 24 h, hemodynamic changes, and postoperative adverse effects. Methods: This prospective, randomized, double-blind study was conducted on a total of 80 women with breast cancer belonging to American Society of Anesthesiologist class I and II scheduled for MRM, which were randomly allocated into two groups – Group R (n = 40) received 0.25% ropivacaine 29 ml + NS 1 ml and Group RD (n = 40) received 0.25% ropivacaine 29 ml + dexamethasone (4 mg) 1 ml. Ten milliliters of the study drug was used in Pecs I and the rest 20 ml in Pecs II block posttumor resection. Results: The duration of analgesia was statistically significantly longer in RD (778.75 ± 55.12 min) compared to Group R (412.63 ± 21.69 min) (P < 0.05). Pain scores were significantly less in Group RD. The mean dose of acetaminophen required was significantly less in Group RD (2362.50 ± 375.32 mg) than in Group R (3525.00 ± 298.50 mg) (P < 0.05). The incidence of adverse events was similar in both groups. Conclusion: The addition of dexamethasone with ropivacaine in the Pecs block can be used for prolonging the effective duration of analgesia and decreasing postoperative analgesic consumption with comparable hemodynamic and side effect profiles.